MicroRNAs Correlation with Liver Function and Lipid Profiles Among Hepatitis C Virus (HCV) Patients as Diagnostic Biomarkers - Lubna Hussein Murshed; Jaleel Samanje; Zaidan Hassan, Dr. Athraa; AL-Waisy, Dr. Safa. A. (Diyala Journal of Medicine, 2025)
Background: MicroRNAs have been concerned in modulating multiple stages of HCV life cycles and specific miRNAs have been identified to be deregulated during HCV infection and serve as essential mediators for the antiviral treatment. Objectives: To understand the role of circulating serum microRNAs (miR-21-5p and miR-196-5p) in correlation with liver function tests and lipid profiles as diagnostic markers in patients with different stages of hepatitis C virus (HCV). Patients and Methods: 150 cases—100 with the Hepatitis C virus and 50 healthy as a control group—are involved. The patients' and the control group's serum levels of miR-21-5p and miR-196-5p were assessed using quantitative real-time PCR (qRT-PCR), and the biochemical tests were measured using a standard automatic biochemistry analyzer (Thermo Fisher 240 V Indiko Plus Clinical Chemistry Analyzer, Kerala, India). Results: Serum miR-21-5p is upregulated in patients with acute and chronic HCV compared with the control group, while serum miR-196-5p is upregulated in acute HCV, HCV induced liver cirrhosis and sustained virologic response patients compared to the control group. The maximum serum total cholesterol (TC), TG, LDL and VLDL levels were in SVR and the minimum levels were in HCV-LC, the highest LFTs levels were in the AHC group. MiR-196-5p was negatively correlated with TG and VLDL in AHC and HCV-LC. The ROC curve showed the highest sensitivity and specificity for miR-21-5p in the AHC and CHC groups, while the highest sensitivity and specificity for miR-196-5p was in the AHC, HCV-LC, and SVR groups. Conclusion: Increased serum miR-21-5p and miR-196-5p expression in HCV patients implicated in lipid dysregulation within hepatocytes and monitoring this correlation might be used as biomarker of disease progression and liver dysfunction. Keywords: HCV, miR-21-5p, miR-196-5p, Circulating, Biomarker.